Report on mineral exploration in Iscaycruz (Oyon) area: consolidated report - Japan International Cooperation Agency (1985)
This report summarizes results of the exploration works of the progressive stage of the Mineral Exploration by means of drilling and tunnelling explorations carried out during the period of three years from 1982 to 1984 in the lscaycruz Area (40 km2), the Republic of Peru. The lscaycruz Area had been extracted as a favorable arca where economic ore deposits would be expected to be emplaced, by the results of the early stage of the Mineral Exploration in the Oyon Arca (860 km2), which was carried out during the period of three years from 1979 to 1981. The purpose of this project is to confirm the existence of economic ore deposits, in the selected areas of Limpe area and Limpe-South area in the lscaycruz Arca, through the implement of investigations such as tunnelling exploration and drilling exploration both on the surface and in the underground. The Iscaycruz Arca is located about 150 km north of Lima, in the backbone range of the Western Andes. Geologically, Mesozoic sedimentary rocks are widely distributed in this area, forming remarkable composit folded structure due to tight folding with the axes in the Andean direction, namely NNW-SSE. The lscaycruz mineralized zone is located approximately 7 km south-southeast of Oyon, in the high mountain at the altitude of 4,700 m above sea level. The mineralization occurs in the limestones of the Santa Formation, about 50 to 100m in thickness, and continues about 12 km along the strike. In this mineralized zone, ore deposits are divided roughly into two categories; the one is contact metasomatic skarn type ore deposits represented by copper-zinc skarn orebodies and the other is hydrothermal replacement ore deposits represented by copper-lead-zinc massive sulphide orebodies as well as by disseminated orebodies of lead and zinc in the siderite beds. The cummulative amount of the investigation in this survey project is; as to the tunneling exploration, 2,008 m is the total excavation length of the Adit-N (835 m, at 4,090 m above sea level) and of the Adit-S (1 ,173 m, at 4,570 m above sea level); andas to the drilling exploration, 4,110 m of 19 holes is the total length of the surface drilling (2,040 m, 9 holes) and the underground drilling (2,070 m, 10 holes). Through the drilling exploration, indications of mineralization have been confirmed in all the hales; especially, in the 4 surface drill holes and in the 4 underground drill holes located in the Limpe area as well as in the 2 surface drill holes in the Limpe-South arca, were confined high grade orebodies with the thickness over 10 m, the grade of which is as high as 20% Pb, Zn and Cu combined. Also, in the tunnelling exploration, high grade orebodies have been confirmed at three localities and the conditions of the emplacement of the orebody’s have been clarified. Considering the results of these exploration works generally, it is estimated that the sizes of the orebodies in the Limpe area are 300 m in horizontal extension, over 150m in vertical extension and 10 to 30 m in thickness. By the result of the ore reserve estimation by polygon method, the expected ore reserves in this area is estimated to be 3,250 thousand tons with the grade as high as 20% Pb and Zn combined. As for the mineralization in the Limpe area, it would be necessary to conduct further detailed exploration works for the confirmation of the ore deposits, the ore reserves and possible extension of the orebodies at the depth. Also, it would be necessary to continue exploration for potentialities of mineral resources in the Lirnpe-South arca, Limpe-North area and Kunsha Punta arca. As to the investigation of the next stage, it is recommended to carry out the survey for the planning of the development including every item in necessary fields for the investment to the development of mineral resources.